دراسة الخصائص المكانية والزمنية للجفاف في المنطقة الساحلية من سوريا خلال الفترة 1966- 2008 - سكاف ميشيل; حمدان سلاف (Latakia University Journal -Biological Sciences Series, 2013)
يعد الجفاف أحد أهم التحديات التي تواجه التنمية المستدامة في مناطق شرق المتوسط حيث الموارد المائية محدودة أصلا والنظم البيئية هشة . تم استخدام محصلات الانحرافات القياسية الشهرية المثقلة للهطل لتقدير الشدة والتكرار والامتداد المكاني لجفاف الموسم الماطر(أيلول – ايار ) لخمس محطات مناخية تغطي جزءا مهماً من المنطقة الساحلية خلال الفترة من عام 1966 حتى 2008، وقد تم التحقق من تغير شدة الجفاف باستخدام الانحدار الخطي واختبار مان كندال . أظهرت النتائج أن الجفاف يتكرر بشكل كبير في جميع أجزاء المنطقة الساحلية ( بنسبة تصل إلى 35 % في بعض الأجزاء ) لكن بشدات مختلفة وقد يمتد لثلاثة مواسم متتالية كما حدث خلال الفترة 1988-1991 .كما أن الجفاف متطرف الشدة يمكن أن يشمل كامل المنطقة كما حدث في الموسم 1972-1973 . بينت النتائج من جهة أخرى تزايد شدة الجفاف بسبب تناقص قيم المؤشر بمقدار تراوح بين 0.29 و0.96 في المحطات المدروسة الأمر الذي سيكون له تأثيرات بيئية واقتصادية كبيرة ويشكل تحدياً متزايداً أمام الإنتاج الزراعي وإدارة الموارد المائية في المنطقة . Drought is one of the most important challenges facing sustainable development in eastern Mediterranean regions, where water resources are already limited and ecosystems are fragile. Sums of weighted standardized monthly precipitation anomalies were used to assess annual drought intensity, frequency and spatial extent in five climatic stations located in Syrian coastal region during the period 1966-2008.Changes in drought intensity were detected using trends with Mann – Kendall test. Results show that drought occurs with high frequency over all parts of the coastal region(up to 35% in some parts),but with different intensities.Extreme drought can hit all regions in some years as happened in 1972-1973. Moreover drought may strike the same region for three consecutive years (1988-1991). Also the results show an increasing tendency in drought intensityrelated to the decreasein drought index values (between 0.29-0.96). This can have serious ecological and economic consequences and will pose an increasing challenge to agriculture and the management of water resources in this region.